PKM Pembuatan E-Commerce Desa Banjarsari - Tholib Hariono; Hilyah Ashoumi; Habib Qoirul Tabiin; Mochammad Khoirul Faizin (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
Based on the situation analysis as previously described, also based on the results of interviews and observations in Banjarsari village, the problems faced by partner businesses can be identified as follows: (1) production is still limited; (2) do not have a workforce; and (3) conventional marketing only relies on word to mouth. The method of dedication to PKM is making e-commers through; Area Observation, Need Identification, Goal Setting, Implementation, Assistance and Evaluation. Based on the process of community service activities that have been carried out, the outputs that have been achieved are: Village e-commerce which can be accessed via the https://ecommerce.banjarsari-jbg.desa.id link and the completion of the Banjarsari village UMKM data, as well as training and assistance in use e-commmers in banjarsari village.